Answer:
x = - 3
Explanation:
using the slope formula
m =
![(y_(2)-y_(1) )/(x_(2)-x_(1) )](https://img.qammunity.org/2023/formulas/mathematics/college/jkzrkt8zi557egkc0ias6wietjfal5swo6.png)
with (x₁, y₁ ) = (x, 4 ) and (x₂, y₂ ) = (- 3, 8 )
m =
![(8-4)/(-3-x)](https://img.qammunity.org/2023/formulas/mathematics/high-school/mjjm55i4jckka6ln2v2yiigt8i07gkt5nx.png)
since m is undefined, then the denominator must be zero, since division by zero is undefined , then equating the denominator to zero
- 3 - x = 0 ( add 3 to both sides )
- x = 3 ( multiply both sides by - 1 )
x = - 3